La civilisation des Champs d'Urnes Étude critique dans le Bassin parisien - Brun, Patrice (Documents d'archéologie française, 1986)
In this book Patrice Brun critically examines the "Urnfield Culture" concept and the migration model that it implies. After reexamining the Paris Basin evidence, he presents a comparative study of closed finds from outside the region As a result, the traditional interpretation is rejected. Two clear breaks are evident in the development of material culture between the 13th and 7th centuries B.C. These breaks coincide with major socio-economic changes which. Far from being restricted to the Paris Basin, affect a large part of Europe. They also coincide with the transformations that led to the emergence of urban civilisations in Greece and Italy.